STK15 Phe31Ile and Val57Ile polymorphisms increase the risk of gastrointestinal cancer - Lai, Tianxin; Chong, Eric Tzyy Jiann; Chuah, Jitt Aun; Chua, Kek Heng; Lee, Ping-Chin (Penerbit Universiti Kebangsaan Malaysia, 2018)
STK15 is a serine/threonine kinase that regulates chromosomal segregation during mitosis. Single nucleotide polymorphisms (SNPs) in this gene, Phe31Ile (rs2273535) and Val57Ile (rs1047972), are inconsistently associated with gastrointestinal cancer (GIC) across different populations. However, this association is unclear in Malaysian population. Therefore, this study investigated the association of STK15 Phe31Ile and Val57Ile polymorphisms to GIC risk in Malaysia. Genomic DNA was extracted from 185 GIC patients and 1110 healthy controls and was subjected to polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis. SNPs were further confirmed using sequencing. We found that the 31Phe allele and 31Phe/Phe genotype in the Phe31Ile SNP significantly increased GIC risk in Malaysian population, particularly in gastric cancer (p<0.017). The combined analysis for both SNPs also increased the risk of GIC in this study. Etiological factors such as age, gender and ethnicity were not associated with GIC in the population. This is the first study to report the association of STK15 Phe31Ile and Val57Ile SNPs with an increased risk of GIC in Malaysians; the 31Phe allele is exclusively associated with the risk of gastric cancer. In addition, GIC incidences among Malaysians have significantly shifted to a younger age (<50 years).